Tissue localization of natural killer cells dictates surveillance of lung metastasis - Vermeer, Marijne; Sparano, Colin; Coianiz, Nicolò; Mayoux, Maud; Litscher, Gioana; Fonseca, André; Dergun, Stanislav; Mussak, Caroline; Rindlisbacher, Lukas; Häne, Philipp; Ducimetière, Laura; Wertheimer, Tobias; et al. (Nature Communications, 2025)
The lung is a common metastatic site for various cancer types. Successful immune surveillance of lung metastasis depends on Natural Killer (NK) cells, but the underlying mechanisms are elusive. Here, we show that the pulmonary vasculature recruits and maintains highly cytotoxic, differentiated CD11bhigh NK cells through the integrins Lymphocyte Function-associated Antigen 1 (LFA-1) and Very Late Antigen (VLA-4). These NK cells rapidly eradicate metastasizing tumor cells within the vasculature. However, after the initial clearing phase, differentiated pulmonary NK cells largely remain intravascular and fail to track extravasated tumor cells. In contrast, metastatic nodules are preferentially infiltrated with circulating, less differentiated CD27high NK cells. Within the metastatic lung, CD11bhigh NK cells undergo a rapid impairment of their migratory and cytotoxic features, while the intranodular CD27high subset transitions towards a transforming growth factor β (TGF-β)-driven state with limited persistence. Our findings demonstrate that the compartmentalization of NK cells is key for effective tumor cell surveillance in lung metastasis and suggests that TGF-β-resistant CD27high NK cells may offer a promising therapeutic avenue to enhance local anti-tumor activity.